Sensasi, Persepsi, dan Emosi - Gustiani Fujia Damayanti; Imas Kania Rahman (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Human development theories regarding sensation, perception, and emotion focus on how individuals respond to and interpret stimuli from the environment and how emotional reactions evolve throughout life. Sensation is the basic process that occurs when the human senses receive physical stimuli from the external world, while perception involves the brain's interpretation and meaning-making of the received information. Emotions, which are psychological responses to both internal and external stimuli, also play a crucial role in individual development. Classical theories, such as Piaget’s and Vygotsky’s developmental theories, as well as those related to cognitive and social development, provide in-depth perspectives on the interaction between sensation, perception, and emotion in shaping human experience. As individuals grow, they develop the ability to process stimuli in more complex ways, forming a more mature understanding of themselves and the world around them. Factors such as social environment, culture, and personal experiences play a significant role in shaping how individuals feel, evaluate, and cope with their emotions. Understanding these theories can help explain how humans adapt, learn, and interact with the world throughout their lives.